Maritime issues in the South China Sea : troubled waters or a sea of opportunity - Hu, Nien-Tsu Alfred; McDorman, Ted L. (Abingdon, Oxon : Routledge, 2014)
"South China Sea (SCS) issues are complex and dynamic, ranging from historic claims to present day military occupation, from military security to regional stability, from rhetorical appeasements to national interests, from intraregional competition to extraregional involvement. The submissions made in 2009 by several Southeast Asian states to the United Nations Commission on the Limits of the Continental Shelf (CLCS) respecting outer limits of extended continental shelves beyond 200 nautical miles in the South China Sea resulted in renewed attention to the maritime disputes over the insular features and the waters of the South China Sea among several claimant States. Questions have resurfaced about the future of cooperation in the region. Furthermore, the improvement of cross-Strait relations between Taiwan and China after 2008 has added a new element to the evolution of South China Sea issues. This book describes these recent developments in depth and provides an examination of possible future developments in the South China Sea"--Provided by publisher.
South China Sea : troubled waters or a sea of opportunity? / Nien-Tsu Alfred Hu -- Maritime delimitation in the South China Sea : potentiality and challenges / Robert W. Smith -- A strategic perspective on security and naval issues in the South China Sea / Chris Rahman and Martin Tsamenyi -- ROC's maritime claims and practices with special reference to the South China Sea / Kuan-Hsiung Wang -- The South China Sea workshop process and Taiwan's participation / Yann-huei Song -- Regional cooperation in marine environmental protection in the South China Sea : a reflection on new directions for marine conservation / Aldo Chircop -- Towards establishing a Spratly Islands international marine peace park : ecological importance and supportive collaborative activities with an emphasis on the role of Taiwan / John W. McManus, Kwang-Tsao Shao, and Szu-yin Lin -- Semi-enclosed troubled waters : a new thinking on the application of the 1982 UNCLOS Article 123 to the South China Sea / Nien-Tsu Alfred Hu -- Post-2009 : an overview of recent developments concerning the South China Sea / Ted L. McDorman and Nien-Tsu Alfred Hu.
Reprint. Originally published: 2013.
Includes bibliographical references and index.
Keywords: Law of the sea -- South China Sea; South China Sea -- Boundaries